OPINI AUDIT SEBAGAI PEMODERASI PENGARUH UKURAN PERUSAHAAN PADA AUDIT REPORT LAG - Guna Wijaya, I Gede; Supartha Wisadha, I Gede (E-Jurnal Akuntansi; Vol 14 No 1 (2016), 2016)
Audit report lag measured by the span of the completion of the audit of annual financial statements from the date of closing company that is 31 December until the date indicated on the independent auditor's report. This study aims to determine the audit opinion as the moderating influence of firm size on the audit report lag. Population in this research are manufacturing companies listed in Indonesia Stock Exchange 2011-2013. The samples used as much as 61 companies by purposive sampling method. The analysis technique used is Moderated Regression Analysis (MRA). Statistical analyzes were used: (1) the classical assumption test, (2) test the hypothesis. Based on the analysis and hypothesis testing, it is concluded that (1) company size have negative influence on audit report lag, (2) Audit opinion have negative influence on audit report lag, (3) audit opinion able to moderate (strengthen) influence of company size on the audit report lag.
Keywords: audit report lag, ukuran perusahaan, opini audit